2011
DOI: 10.1016/j.cub.2011.08.049
|View full text |Cite
|
Sign up to set email alerts
|

The Tubulin Deglutamylase CCPP-1 Regulates the Function and Stability of Sensory Cilia in C. elegans

Abstract: Summary Background Post-translational modifications (PTMs) such as acetylation, detyrosination, and polyglutamylation have long been considered markers of stable microtubules, and have recently been proposed to guide molecular motors to specific subcellular destinations. Microtubules can be deglutamylated by the cytosolic carboxypeptidase CCP1. Loss of CCP1 in mice causes cerebellar Purkinje cell degeneration. Cilia, which are conserved organelles that play important diverse roles in animal development and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(187 citation statements)
references
References 36 publications
8
179
0
Order By: Relevance
“…In line with this idea, knockdown of polyglutamylase PGs1 in ROSA22 mice decreases the localization of KIF1A to neurites [103]. Further, the ciliary localization of kinesin 3 KLP 6 in C. elegans is positively regulated by tubulin deglutamylase CCPP 1 [104]. However, in COS cells, the truncated, constitutively active KIF1A(1 393) was a non selective motor [105].…”
Section: Specificity For a Subset Of Microtubule Tracksmentioning
confidence: 60%
“…In line with this idea, knockdown of polyglutamylase PGs1 in ROSA22 mice decreases the localization of KIF1A to neurites [103]. Further, the ciliary localization of kinesin 3 KLP 6 in C. elegans is positively regulated by tubulin deglutamylase CCPP 1 [104]. However, in COS cells, the truncated, constitutively active KIF1A(1 393) was a non selective motor [105].…”
Section: Specificity For a Subset Of Microtubule Tracksmentioning
confidence: 60%
“…In this present report we demonstrate that apical trafficking of soluble, raftassociated or non-associated cargo proteins can be modulated by TTL expression and alterations in intracellular detyr-tubulin, which suggests that stable detyrosinated microtubules serve as tracks for kinesin-driven post Golgi transport to the apical membrane domain of MDCK cells, especially considering that kinesin motors do not move preferentially along dynamic microtubules (Cai et al, 2009). Recent data on the function and stability of sensory cilia in C. elegans support the idea of posttranslationally modified microtubules that guide molecular motors to specific subcellular destinations (O'Hagan et al, 2011). The authors propose that these tubulin modifications regulate the velocity of kinesin-2 motors.…”
Section: Discussionmentioning
confidence: 84%
“…Disruption of tubulin dynamics can cause mitochondrial dysfunction and lead to neurodegeneration (52). Recently, using Caenorhabditis elegans as an animal model, it was shown that tubulin deglutamylation by CCP1 regulates localization and activity of molecular motors in cilia (53). Changes in tubulin processing can potentially explain the myriad defects found in pcd mice, including abnormal accumulation of polysomes (9), altered transcription and DNA repair (10,11), endoplasmic reticulum stress (12), formation of axonal spheroids (13), mitochondrial dysfunction (14), elevated autophagy (15), and abnormal dendritic development (16).…”
Section: Discussionmentioning
confidence: 99%